Intranasal Nystatin Therapy in Patients with Chronic Illness Associated with Mold and Mycotoxins (Global Journal of Medical Research, 2015)
We have previously reported that patients with chronic illness frequently had a history of prior exposure to water damaged buildings (WDB) and mold. These patients were found to have elevated levels of mycotoxins in the urine. We postulated that the mycotoxin producing molds colonize the sinuses of these patients and lead to chronic symptoms. In a recent observational analysis of patients treated with intranasal antifungal agents, either amphotericin B (AMB) or itraconazole (ITR), we showed that 94% of these patients improved clinically (AMB group). We also found that the urine mycotoxin levels decreased substantially in patients that improved on therapy. However, AMB was associated with local (nasal irritation) adverse effects (AE) in 34% of the cases, which resulted in discontinuation of therapy. The present study expands these treatment observations in which patients intolerant to AMB were treated with intranasal nystatin (NYS). We found very promising improvements with this agent as well. No local (nasal) AE were seen with NYS.
Keywords: toxic mold; mycotoxin; chronic fatigue syndrome; intranasal antifungal therapy; nystatin